2015
DOI: 10.1016/j.bbi.2015.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Altered fecal microbiota composition in patients with major depressive disorder

Abstract: Studies using animal models have shown that depression affects the stability of the microbiota, but the actual structure and composition in patients with major depressive disorder (MDD) are not well understood. Here, we analyzed fecal samples from 46 patients with depression (29 active-MDD and 17 responded-MDD) and 30 healthy controls (HCs). High-throughput pyrosequencing showed that, according to the Shannon index, increased fecal bacterial α-diversity was found in the active-MDD (A-MDD) vs. the HC group but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

104
1,294
23
35

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,813 publications
(1,562 citation statements)
references
References 49 publications
104
1,294
23
35
Order By: Relevance
“…109 However, another recent study examined the composition of fecal microbiota in 46 patients with depression and 30 healthy controls, and reported significant differences with increased population of Bacteroidetes, Proteobacteria, and Actinobacteria, and decreased population of Frimicutes in patients with depression. 110 Other evidence that might suggest a role for gut microbiota in the pathogenesis of depression is from studies that have shown certain probiotics can alleviate depressive symptoms in rodent models. Rats that are exposed to stress in early stages of life show behavior traits that are consistent with mood disorder that persists through their adulthood.…”
Section: Gut Microbiota and Depressionmentioning
confidence: 99%
“…109 However, another recent study examined the composition of fecal microbiota in 46 patients with depression and 30 healthy controls, and reported significant differences with increased population of Bacteroidetes, Proteobacteria, and Actinobacteria, and decreased population of Frimicutes in patients with depression. 110 Other evidence that might suggest a role for gut microbiota in the pathogenesis of depression is from studies that have shown certain probiotics can alleviate depressive symptoms in rodent models. Rats that are exposed to stress in early stages of life show behavior traits that are consistent with mood disorder that persists through their adulthood.…”
Section: Gut Microbiota and Depressionmentioning
confidence: 99%
“…A clear 'proof of concept' that microorganisms can induce anxiety was demonstrated in mice, by the anxiety-like behavior induced by some enteric bacterial pathogens [7][8][9] (Figure 1). Moreover, inflammation and CMI activation in human subjects with some types of MDD likely result from overgrowth and intestinal translocation of Gram-negative enterobacteria due to a leaky gut [11,13] (Figure 1). More research is needed to identify and/or characterize such kind of pathobionts (potentially pathological microorganisms which, under normal circumstances, live as symbionts) susceptible to induce depression or anxiety in humans.…”
Section: Resultsmentioning
confidence: 99%
“…Jiang et al [13] recently reported an altered fecal microbiota composition in patients with MDD (Proteobacteria, Bacteroidetes, and Actinobacteria were significantly more abundant, whereas levels of Firmicutes were significantly reduced; it is important to mention that patients were treated with antipsychotics, a study limitation acknowledged by the authors). The overgrowth of the phylum Proteobacteria [13] included the above inflammogenic Enterobacteriaceae identified by Maes et al [11].…”
Section: Evidence For Inflammatory Depressive Actions Induced By Gutmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced levels of gut permeability and associated alterations in gut microbiota are linked to the etiology and/or course of an array of medical conditions, including multiple sclerosis (13), Parkinson's disease (12), dementia (14), schizophrenia (15), bipolar disorder (16), the autistic spectrum (17) and depression (18). As noted above, the high rates of comorbid depression, often prior to symptom exacerbation, in these conditions suggests that gut-brain axis alterations may mediate some of their associations with such an array of medical presentations via raised levels of depression.…”
Section: The Gut-brain Axismentioning
confidence: 99%